Male circumcision as strategy for HIV prevention and sexually transmitted diseases: the potential role of traditional birth attendants in neonatal male circumcision - Catia Dini (Istituto Superiore di Sanità, 2010)
In developing countries, it would be advisable to give priority to human immunodeficiency virus (HIV) prevention strategies, because of the high mortality caused by the rapid spread of the pandemic. Furthermore, HIV prevention could contribute to the mitigation of tuberculosis (TB) propagation, which is tightly correlated to acquired immune deficiency syndrome (AIDS). As demonstrated, male circumcision (MC) confers protection against HIV and sexually transmitted diseases (STD). The suggested strategy considers the neonatal MC advantageous, since it is safer, feasible, culturally more acceptable and less costly than adult MC. This approach is based on the assumption that, if newborn males are circumcised, within the next 15-20 years the sexually active population will be almost entirely circumcised and, consequently, the HIV transmission will be reduced. The employment of retrained traditional birth attendants is considered in order to implement the MC after the child birth and to facilitate its acceptance in those contexts where it is not traditionally performed.